Inactivation of Nucleus Reuniens Impairs Spatial Memory in Mice - (:unkn) unknown (My University, 2020)
Episodic memory is a complex process requiring input from several regions of the brain. Coordinated activity in the Dorsal Hippocampus (DH) and medial Prefrontal Cortex (mPFC) is required for episodic memory consolidation. Our laboratory demonstrated that simultaneous subthreshold chemogenetic inactivation of the dorsal hippocampus (DH) and medial prefrontal cortex (mPFC) impairs the consolidation of object placement (OP) and object recognition (OR) memory in female mice (Tuscher et al., 2018), suggesting that these two brain regions work in concert to promote memory consolidation. However, the mechanisms through which the DH and mPFC interact to promote memory consolidation remain poorly understood. A growing body of research suggests that the Nucleus Reuniens of the thalamus (RE) is one of several structures that facilitate communication between DH and mPFC during memory and may do so through bidirectional excitatory projections to both regions. Furthermore, recent work from other labs indicates that the RE is necessary for spatial working memory and fear extinction learning. However, it is not clear to what extent the RE is necessary for OR and OP memory. The goal of this study was to determine whether activity in the RE is necessary for OP and OR memory. Kappa-opioid receptor DREADD (KORD) virus activated by salvinorin B was used to inactivate excitatory neurons in the RE. Mice infused with GFP virus or saline were used as controls. During training, mice were allowed to explore 2 identical objects placed near the corners of a large white box, and received a 10 mg/kg injection of salvinorin B either 10 minutes prior to training or immediately after training to target effects to the encoding and consolidation phases of memory, respectively. Testing was conducted 4h after training for OP or 24h for OR, timepoints at which control mice remember the location of training objects. During testing, one object was moved to a different quadrant of the testing box. Activation of the KORD prior to or immediately after training blocked OP memory relative to chance and controls. To determine the effect of RE inactivation on neuronal activity, expression of the immediate early gene EGR-1 was measured via fluorescent immunohistochemistry 1 hr after an object training trial. Object training alone did not increase EGR-1 expression relative to homecage controls, but KORD activation of RE resulted in a small but significant decrease in EGR-1 expression. In summary, the findings of this study support a key role for the RE in spatial memory learning and consolidation.
Keywords: Nucleus Reuniens; spatial memory